2012
DOI: 10.2478/v10032-012-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

The Alleviation Effect of Silicon on Seed Germination and Seedling Growth of Tomato Under Salinity Stress

Abstract: This study was conducted to evaluate the effectiveness of silicon (Si) application under salinity levels on seed germination and growth characteristics of tomato seeds. A laboratory experiment was performed on completely randomized design with two levels of salinity (25 and 50 mM NaCl) and 2 concentration of Si (1 and 2 mM) with 4 replications. Germination percentage, germination rate, seedling shoot and root length, fresh and dry weight of seedling and mean germination time was measured. Seed germination of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
3
18
0
2
Order By: Relevance
“…Yasmeen et al (2015) reported that AgNPs [36]. Drastically, decrease in VI and TI are in conformity with other reports [37,38]. Haghighi et al (2012), reported that tomato plants exposed to nano silicon showed significant decrease in VI, also copper and zinc significantly decreased seedling vigor, TI, germination percentage, shoot and root lengths in tomato plants [37].…”
Section: And Tisupporting
confidence: 91%
See 1 more Smart Citation
“…Yasmeen et al (2015) reported that AgNPs [36]. Drastically, decrease in VI and TI are in conformity with other reports [37,38]. Haghighi et al (2012), reported that tomato plants exposed to nano silicon showed significant decrease in VI, also copper and zinc significantly decreased seedling vigor, TI, germination percentage, shoot and root lengths in tomato plants [37].…”
Section: And Tisupporting
confidence: 91%
“…Drastically, decrease in VI and TI are in conformity with other reports [37,38]. Haghighi et al (2012), reported that tomato plants exposed to nano silicon showed significant decrease in VI, also copper and zinc significantly decreased seedling vigor, TI, germination percentage, shoot and root lengths in tomato plants [37]. Marked decrease in the growth parameters such as TI, VI, plant weight, length of shoot and root was seen in hyacinth bean seedlings exposed to heavy metal Cadmium [38].…”
Section: And Tisupporting
confidence: 75%
“…This was accompanied by a decrease in the Na + content ( Figure 3 ) and an increase in the K + content ( Figure 4 ) and thus an increase in the K + /Na + ratio ( Figure 5 ), which ultimately led to an improvement in the wheat growth and yield under salt stress [ 2 ]. In agreement with these observations, several studies have shown that the addition of Si could protect the growth and yield of many agricultural crops from the toxic effect of salinity stress [ 43 , 44 , 45 ]. This improvement could be illustrated by reducing the damage effects of accumulated Na + on the plasma membrane integrity via the enhancement of K + /Na + discrimination [ 2 ], stimulation of gene expression [ 14 ] and/or stimulation of the ROS scavenging system [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 66%
“…The NP seed treatments improved water uptake and utilization, and enhanced nutrient availability for seeds from soil . In tomato and squash, seed treatment with nano‐SiO 2 when plants encountered NaCl stress enhanced sprouting and stimulated antioxidant activities. Soil application of SiO 2 NPs at 10 mL L −1 improved chlorophyll content, leaf dry weight, and proline accumulation .…”
Section: Np Effects On Plant Growth and Mechanism Of Actionmentioning
confidence: 99%